Rett syndrome: a clinical case - A. V. Burlutskaya; A. S. Ivanenko; A. V. Statova (Кубанский научный медицинский вестник, 2021)
Background. Rett syndrome is a rare genetic disorder often mimicked by variant other illnesses, which hampers its timely diagnosis. Although knowledge of this pathology has grown remarkably over the past two decades, an appropriate diagnosis is necessary to exclude similar disease phenotypes and select an applicable therapy.Clinical Case Description. A 3-yo girl was admitted with a loss of earlier motor skills. The girl had neurological monitoring since month 2 of age for a delayed psychomotor development and had courses of neurotropic and reconstructive therapy, ineffective. At 18 months she was diagnosed with infantile cerebral palsy, residual period, atonic-astatic form, grade 3, rehabilitation therapy ineffective. With the disease progression and loss of motor skills, the girl was referred to the Bochkov Research Centre for Medical Genetics for sequence genotyping of the MECP2 gene, which determined a heterozygous single-nucleotide polymorphism c.468C>G (p.D156E) diagnostic of the Rett syndrome. The Rett syndrome has poor prognosis for progressive motor and neurological deficiency and eventual severe mental retardation. Patients with the Rett syndrome can have life expectancy of up to 40—50 years with appropriate care but incur a high risk of sudden death.Conclusion. The Rett syndrome is a rare disorder manifested by loss of earlier developed motor and speech skills. This report provides a clear case description and illustrates the difficulty of the syndrome timely diagnosis aggravated by a lack of specific paraclinical signatures. Molecular genotyping techniques allow a proper diagnosis and prognosis assessment in this pathology.